Girls of Riyadh - Alsanea, Rajaa; Translated by Alsanea, Raja and Booth Marilyn (New York Penguin Press, 2007)
This debut novel, banned in the author's own country, reveals the social, romantic, and sexual tribulations of four young women from the elite classes of Saudi Arabia. Every week after Friday prayers, the anonymous narrator sends an email to the female subscribers of her online chat group. In fifty such emails over the course of a year, we witness the tragicomic reality of four university students negotiating their love lives, their professional success, and their rebellions, large and small, against their cultural traditions. The world these women inhabit is a modern one that contains "Sex and the City," dating, and sneaking out of their parents' houses, and all this causes the girls to collide endlessly with ancient customs. The never-ending cultural conflicts underscore the tumult of being an educated modern woman growing up in the 21st century amid a culture firmly rooted in an ancient way of life.--From publisher description